Antioxidative Responses in Banana (Musa Sp.) Cultivars Under Water Stress - Chai, Tsun Thai (2003)
Responses of the enzymatic and non-enzymatic antioxidant defence systems as well as oxidative injury in banana ptants (Musasp.) subjected to polyethylene glycol (PEG)-induced water stress were investigated. Micropropagated plantlets of two banana cultivars, '8erangan' and 'Mas' were subjected to 0%, 10%, 20% and 40% PEG 6000 treatments in vitro for a duration of 14 days. Progressive decline in the leaf water content of both cultivars with time and increased concentrations of PEG used, indicates that water stress was successfully imposed. Based on the enhanced levels of lipid peroxidation and membrane permeability, this study shows that water stress resulted in oxidative injury in both cultivars. Relatively lower level of membrane leakage and malondialdehyde concentrations in 'Berangan' indicate that it was more tolerant than 'Mas' to water stress-induced oxidative damage.